2008
DOI: 10.1002/pmh.47
|View full text |Cite
|
Sign up to set email alerts
|

Defence mechanisms in schizophrenia

Abstract: Aim In this study, the aim was to conduct an empirical study of the nature of defence mechanisms in a group of subjects with schizophrenia. Methods Forty-four clinically stable, medicated subjects with schizophrenia completed the Response Evaluation Measure (REM-71), a self-report measure used to assess defence mechanisms, and were rated with the Brief Psychiatric Rating Scale (BPRS) to assess severity of psychopathology. Responses on the REM-71 were compared with 136 age and gender-matched control subjects. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…755–757), and agreement was reached on all of them. The REM-71 has been used in studies with both adults and adolescents, both from the community (Prunas, Preti, et al, 2014) and from clinical samples with various forms of behavioral or emotional problems, including self-injurious behaviors (Sarno, Madeddu, & Gratz, 2010), schizophrenia (Shaw, Geurse, & Steiner, 2008), and gender dysphoria (Prunas, Vitelli, et al, 2014); it also showed significant associations with various indices of well-being and satisfaction with several life domains (Prunas et al, 2009; Steiner et al, 2001). The validation study of the Italian version of the instrument (Prunas et al, 2009) indicated that both high-order scales showed an acceptable internal consistency (Prunas et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…755–757), and agreement was reached on all of them. The REM-71 has been used in studies with both adults and adolescents, both from the community (Prunas, Preti, et al, 2014) and from clinical samples with various forms of behavioral or emotional problems, including self-injurious behaviors (Sarno, Madeddu, & Gratz, 2010), schizophrenia (Shaw, Geurse, & Steiner, 2008), and gender dysphoria (Prunas, Vitelli, et al, 2014); it also showed significant associations with various indices of well-being and satisfaction with several life domains (Prunas et al, 2009; Steiner et al, 2001). The validation study of the Italian version of the instrument (Prunas et al, 2009) indicated that both high-order scales showed an acceptable internal consistency (Prunas et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Coping with the experience of different realities demands attempts at integration and defence. People with schizophrenic symptoms have immature defence mechanisms, such as negation, repression, fantasy, and splitting ( 63 ) or delusions ( 64 ). The concepts of splitting and disruption in the sense of self in schizophrenia are as old as the concept of schizophrenia itself ( 65 ).…”
Section: Introductionmentioning
confidence: 99%